Low birthweight and subsequent emotional and behavioural outcomes in 12-year-old children from Soweto, South Africa: findings from Birth to Twenty - Sabet, F; Richter, L; Ramchandani, P; Stein, A; Quigley, M; Norris, S (Oxford University Press, 2009)
Background: The fetal origins hypothesis suggests that an adverse prenatal environment, indexed by low birthweight (LBW), may increase the risk of developing later disease. Recently the hypothesis has been extended to psychological outcomes, especially depression. The aim of this analysis was to test, for the first time in a developing country setting, the association between LBW and psychological symptoms, in Soweto, South Africa. Methods: A sample of 1029 children was drawn from Birth to Twenty, a longitudinal cohort followed from pregnancy to young adulthood. This sample completed the Youth Self Report at age 12 years, a validated psychological measure of behavioural and emotional adjustment. Scores were compared between LBW (<2500 g) and normal birthweight children using multivariate analysis with adjustment for potential birth and life events confounding factors. Results: No associations were found between LBW and total [adjusted odds ratio (OR) 1.09, 95% confidence interval (CI) 0.69-1.74], internalizing (adjusted OR 0.81, 95% CI 0.52-1.28) or externalizing profiles (adjusted OR 0.81, 95% CI 0.49-1.36). The only difference detected was for the internalizing sub-profile of Somatic Complaints (adjusted OR 2.02, 95% CI 1.21-3-38), which on subgroup analysis was greatest among females. Conclusions: We found no convincing evidence of an association between LBW and emotional and behavioural outcomes in 12-year-olds in this sample in urban South Africa. To our knowledge, this is the first published assessment of this association in a developing world context.